The metabolic effects of a commercially available chicken peri-peri (African bird's eye chilli) meal in overweight individuals. Issue 5 (11th September 2015) - Kroff, Jacolene; Hume, David J.; Pienaar, Paula; Tucker, Ross; Lambert, Estelle V.; Rae, Dale E.
Abstract: A growing body of evidence suggests that capsaicin ingestion may lead to desirable metabolic outcomes; however, the results in humans are equivocal. Whether or not benefits may be gained from ingestion of capsaicin via a commercially available meal has not been determined. The objectives of this randomised, cross-over intervention study were to compare the 2 h postprandial effects of a standard commercially prepared meal containing chilli (HOT, 5·82 mg total capsaicinoids) with a similar meal with no chilli (CON, <1·0 mg total capsaicinoids) on resting energy expenditure, plasma insulin, glucose, serum high sensitivity C-reactive protein (hs-CRP) concentrations, core body temperature and forearm microvascular reactivity responses in overweight individuals. A total of thirty-four apparently healthy individuals (sixteen men and eighteen women) between 18 and 50 years of age, with a BMI >25 kg/m 2 and a waist circumference >94 cm (men) or 80 cm (women), were studied. Participants had normal glucose tolerance and were accustomed, but were not regular chilli eaters. A paired t test indicated that insulin AUC was smaller following the HOT meal ( P =0·002). Similarly, there was a tendency for glucose AUC to be reduced following the HOT meal ( P =0·056). No discernable effects of the HOT meal were observed on metabolic rate, core temperature, hs-CRP concentrations and endothelial-dependent microvascular reactivity. The results from this study indicate that a standard restaurant meal containing a relatively small dose of capsaicin delivered via African bird's eye chilli, which is currently available to the public, results in lower postprandial insulin concentrations in overweight individuals, compared with the same meal without chilli.